2020
DOI: 10.1183/13993003.01618-2020
|View full text |Cite
|
Sign up to set email alerts
|

Similarities between COVID-19 and anti-MDA5 syndrome: what can we learn for better care?

Abstract: Since the end of 2019, the coronavirus disease 2019 (COVID-19) pandemic has struck worldwide, leading to more than 7 million cases by June 2020, with an approximately 5.5% mortality rate, mainly due to acute respiratory distress syndrome (ARDS) [1].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 13 publications
0
44
0
2
Order By: Relevance
“…COVID-19-associated thromboses, severe lung pathology, and hyperinflammation contribute to poor outcomes. These manifestations bear some similarities to those observed in rheumatic diseases, such as antiphospholipid syndrome, 3 rheumatic-associated lung disease, 4 and macrophage activation syndrome 5 secondary to SLE, for which B-cell depletion with rituximab has been shown to be effective. Antiphospholipid antibodies have also been reported in COVID-19 patients with thromboses, although it is unclear whether these antibodies are pathogenic in this context, 3 and lung CT features in some patients with COVID-19 resemble those of fibrotic organising pneumonia (eg, similar to anti-MDA5 anti-synthetase syndrome).…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…COVID-19-associated thromboses, severe lung pathology, and hyperinflammation contribute to poor outcomes. These manifestations bear some similarities to those observed in rheumatic diseases, such as antiphospholipid syndrome, 3 rheumatic-associated lung disease, 4 and macrophage activation syndrome 5 secondary to SLE, for which B-cell depletion with rituximab has been shown to be effective. Antiphospholipid antibodies have also been reported in COVID-19 patients with thromboses, although it is unclear whether these antibodies are pathogenic in this context, 3 and lung CT features in some patients with COVID-19 resemble those of fibrotic organising pneumonia (eg, similar to anti-MDA5 anti-synthetase syndrome).…”
mentioning
confidence: 56%
“…Antiphospholipid antibodies have also been reported in COVID-19 patients with thromboses, although it is unclear whether these antibodies are pathogenic in this context, 3 and lung CT features in some patients with COVID-19 resemble those of fibrotic organising pneumonia (eg, similar to anti-MDA5 anti-synthetase syndrome). 4 It is plausible that anti-SARS-Cov-2 antibodies or immune complexes might potentially evoke monocyte or alveolar macrophage activation, thereby contributing to sustained secretion of proinflammatory cytokines and the development of pulmonary disease. Therefore, could adaptive immunity contribute to poor outcomes in COVID-19, signalling a role for rituximab?…”
mentioning
confidence: 99%
“…A striking similarity in increasingly being recognized between severe COVID-19 and anti-MDA5 DM with a similar involvement of the lung, skin rashes, fever, fatigue and myalgia. Notably, similar blood cytokine profiles with elevated ferritin and C-reactive protein (CRP) supports the idea that severe COVID-19 may resemble a human model of anti-MDA DM [24][25][26]. The hyperinflammatory response triggered by COVID-19 in susceptible individuals culminates in widespread endothelial dysfunction, vasculopathy and thrombotic manifestations with a pathophysiologic overlap with anti-MDA5 DM [27].…”
Section: Infectionsmentioning
confidence: 81%
“…The melanoma differentiation-associated protein 5 (MDA5) is a receptor capable of detecting different type of RNA molecules [ 68 ]. Anti-MDA5 autoantibodies are associated with a rare disease of amyopathic dermatomyositis [ 69 ]. De Lorenzis et al found anti-MDA5 antibody in SARS-CoV-2-infected patients [ 70 ].…”
Section: Sars-cov-2 and Immune And Autoimmune Reactionsmentioning
confidence: 99%